A combination of chitooligosaccharide and lipochitooligosaccharide recognition promotes arbuscular mycorrhizal associations in Medicago truncatula - Feng Feng (Nature Portfolio, 2019)
Polysaccharide molecules chitooligosaccharides (COs) and peptidoglycan not only activate plant immunity but also trigger plant symbiosis signalling. Here the authors show that a combination of COs and lipochitooligosaccharides (LCOs) act synergistically to suppress immunity and promote symbiosis to facilitate beneficial fungal associations.